Pemanfaatan Teknologi Asistif Dalam Pendidikan Inklusif - Bayu Widyaswara Suwahyo; Punaji Setyosari; Henry Praherdhiono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
Various types of technology offer the necessary support for students with disabilities to study together with normal children in inclusive classes. Students can utilize assistive technology (AT) with disabilities to create independence and confidence when studying with normal children. This study uses article analysis with descriptive content analysis method to explain the role of AT in inclusive classes. The keywords used to search for the articles are “technology assistive,” “inclusion,” and “education. The search results of articles obtained from various journal sites, among others, Google Scholar, Directory Of Open Access Journals, Scopus, Emerald, and Taylor Francis selected forty-three research articles related to the use of AT in Inclusive classrooms to be analyzed. This study found that AT consists of tools and services that support students to improve existing abilities and offset or reduce barriers that may occur. Some TAs are developed for practical use, while other functions can create social interaction to curriculum access. The use of TA in inclusive classrooms universally increases inclusivity in the classroom.